P27 PERORAL ENDOSCOPIC MYOTOMY (POEM) FOR TREATMENT OF ACHALASIA. CLINICAL OUTCOMES OF A SINGLE-CENTER INSTITUTE IN UK. (23rd November 2019) - Vrakopoulou, Gavriella Zoi; Barbieri, Lavinia; Ilczyszyn, Andrei; Hamaoui, Karim; Memos, Nikolaos; Smyth, Edel; Jafari, Jafar; Zeki, Sebastian; Wong, Terence; Dunn, Jason M; Botha, Abraham
Abstract: Aim: Assessment of the clinical outcomes, resolution of dysphagia, incidence of postoperative gastro-oesophageal reflux disease (GORD), and quality of life (QoL) of patients after POEM. Background&Methods: POEM is increasingly performed worldwide for treatment of achalasia proving itself effective and safe. From a prospective database of all POEM's performed in our institution from 2015 to 2018, we extracted data for patients with a minimum follow up period of 6 months. All patients underwent a standardized diagnostic work-up including gastroscopy, barium study and high-resolution manometry (HRM). Postoperatively, they had a surveillance gastroscopy in the 1 st postoperative year. Standardized questionnaires evaluating Eckardt, GERD and achalasia QoL (Urbach) scores were completed before and after POEM. HRM and pH studies were offered to all patients after 6 months. Results: Demographic data and procedure details can be seen in Table1 . The preoperative Eckardt, GERD and Urbach scores changed significantly: the median Eckardt score of 7(4-11) decreased to a median of 1(1-9, p<0.001), the GERD score showed a reduction from 26(8-52) to 5(0-40, p<0.001) and Urbach score from 25(17-30) to 14(10-28, p<0.001). Furthermore, preoperative dysphagia score was significantly reduced from a median of 3(1-3) to a median of 0(0-3). Long-term clinical success (Eckardt score ≤ 3) was 87.2%. Postoperatively, 11 patients (29%) were taking PPI's for chest symptoms. Nine of these agreed to undergo pH studies of whom only 1 had a DeMeester score > 14.5. Conclusion: POEM is an effective and safe treatment option for achalasia with good relief of dysphagia and improvement in patients' QoL.